Behaviors of Leucine and Isoleucine in Ion Mobility‐Quadrupole Time of Flight Mass Spectrometry. Issue 12 (13th November 2015) - Guo, Su; Zhang, Fang; Wang, Haoyang; Zhang, Manyu; Zhang, Zhixu; Zhang, Xiang; Guo, Yinlong
Abstract: In this study, ion mobility separation coupled with tandem mass spectrometry (IM‐tandem MS) was utilized to investigate the ionization behaviors of two amino acids including leucine and isoleucine. Under the electrospray ionization (ESI) mode, two protonation sites in each molecular sturcture caused two forms of protomer. One arose from the amino being protonated (amino‐protomer) and the other from the carboxyl being protonated (carboxyl‐protomer). In the two‐dimensional (drift time, m/z ) spectrum, the protomers had the same mass, but the distinguishable drift times and fragmentation patterns. For the characterization purpose, the theoretical collision cross section (CCS) values of the protomers were calculated and proven to be consistent with the experimental. Moreover, the quantified relationship between the amino acids and their protomers was evaluated. It showed that the abundance of the carboxyl‐protomer was proportional to the concentration of the amino acid, whereas that of the amino‐protomer did not have the same trend. Under the atmospheric pressure chemical ionization (APCI) mode, only the carboxyl‐protomer was observed. In addition, the amino‐protomer and the cluster ions observed under ESI were absent completely. The results demonstrate that the ionization mode impacts heavily on the ionization behaviors of leucine and isoleucine not only on the form of therir protomers but also on the quantified relationship. Abstract :